Resilience in complex socio-ecological systems - Bohan, David A.; Dumbrell, Alex J. (Advances in ecological research ;, 2019)
Resilience in Complex Socioecological Systems, Volume 60, the latest release in the Advances in Ecological Research series, includes specific chapters that cover Ecological Resilience, Socio-economic Resilience in Agriculture, Socio-ecological Resilience, Adaptive Capacity in Ecosystems, Tales of Resilience from iDIV and Resilience/ Robustness in Agro-ecology, and Resilience/Robustness in Agro-ecology, amongst other important topics in ecological research. Provides information that relates to a thorough understanding of the field Deals with topical and important reviews on the physiologies, populations and communities of plants and animals